The Reception of the East in Pavlo Kulish’s art (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article under consideration is focused on the relevance of the works by P. Kulish nowadays, which are full of affirmation of love for one's neighbor and harmony between people of different believes. The works of art, such as “Mahomet and Khadyza”, “Marusia Bohuslavka” and others, became the quintessence of Panteleimon Kulish's quest to prove proximity to the Qur’an and the Bible, a representation of the universal dominants provided with them.  The author notes that the writer was one of the first who discovered the ethical and cultural values of the Islamic world in Christian Ukraine. The poem “Mahomet and Khadyza” is a kind of attempt to convey to the Ukrainian reader basic ideas of Islam, in which Panteleimon Kulish emphasizes their commonality with the Christian.  It is important to note the fact that the bearer of justice and goodness is the woman, Mahomet’s wife Khadyza.  The writer reinterpreted inter-ethnic relations in a new way in his poem “Marusia Bohuslavka”, where the Christian world is depicted through the image of the Ukrainian Marusia, and the Islamic one is of the Turk Osman, who, for the sake of love for a woman, is ready to help her native country.  In this way Panteleimon Kulish tries to change the vector of the reception of the East by the Ukrainians.
Keywords: the East; the Qur’an; the Bible; universal values